Pre-service Teachers Perceptions after Designing TPACK-based Media for 21st Century Learning in Practice Teaching Experience - Islakhah, Farikhatul; Ardini, Sukma Nur; Sugiyanta, Sugiyanta (Universitas PGRI Semarang, 2023)
There are three research objectives in this research. First, to find out the pre-service teachers perception of using Technological Pedagogical Content Knowledge (TPACK)-based media in their teaching practice. Second, to explore technological content knowledge TCK-based media which pre-service teachers used in their teaching and learning. Third, to describe the challenges that the pre-service teachers face in practice teaching experience. This research used descriptive qualitative method. The subject of this research consists of 25 pre-service teachers. The data of this research were collected by using questionnaires and interviews. The questionnaire consisted of closed-ended questions using a Likert scale to measure participants' perceptions related to TPACK implementation. The responses from the questionnaire were analyzed using pie charts to visually represent the distribution of responses. Additionally, interviews were conducted to validate the questionnaire responses and gain further insights into the use of TPACK-based media. The findings of the study indicated that pre-service teachers held positive perceptions of TPACK-based media. They reported implementing TPACK-based learning approaches, successfully overcoming design challenges, and observing improved student engagement and comprehension. The study underscores the importance of technological content knowledge (TCK) utilized by pre-service teachers during their teaching experience. By examining the development and practical application of TPACK, the research aims to contribute to the design of professional development programs that enhance pre-service teachers' technical pedagogical knowledge.